2014
DOI: 10.1002/aic.14317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excluded volume and hydrodynamic interactions on the behavior of isolated bead‐rod polymer chains in shearing flow

Abstract: A detailed study of the effects of hydrodynamic interaction (HI) and excluded volume (EV), on isolated bead‐rod chains in shear flows, where the “rods” are mimicked by stiff Fraenkel springs is presented. It is observed that the deformation behavior at weak and intermediate shear rates is qualitatively similar to that observed for polymer chains in the absence of EV and HI, while that at high‐shear rates is sensitive to modeling details and chain resolution. Our simulations with varying degrees of resolution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 11 publications
20
27
0
Order By: Relevance
“…In the case of shear flow, theoretical predictions have shown that the finite length of a chain leads to shear thinning [8]. On the other hand, shear thinning can also be caused by other phenomena such as excluded volume and hydrodynamic interactions [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], that are not related to chain length. These observations clearly suggest that there are both universal and non-universal contributions to shear thinning, and that separating their influence while interpreting experimental measurements can be tricky.…”
Section: Shear Flow 311 Dilute Solutionsmentioning
confidence: 99%
“…In the case of shear flow, theoretical predictions have shown that the finite length of a chain leads to shear thinning [8]. On the other hand, shear thinning can also be caused by other phenomena such as excluded volume and hydrodynamic interactions [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], that are not related to chain length. These observations clearly suggest that there are both universal and non-universal contributions to shear thinning, and that separating their influence while interpreting experimental measurements can be tricky.…”
Section: Shear Flow 311 Dilute Solutionsmentioning
confidence: 99%
“…19 Prakash et al found that the EV interaction can suppress the orientation of the polymers along the flow direction. 23,24 For ring polymers, the close topology results in higher monomer density, and EV interaction shows a stronger impact. 23,24 For ring polymers, the close topology results in higher monomer density, and EV interaction shows a stronger impact.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, Larson et al found that the scaling exponent of tumbling (TB) frequency against the Peclet number of linear polymers is 2/3 in the presence of HI, unaffected by the EV interaction. [22][23][24][25][26] According to recent studies, the ring polymer has one more tank-treading (TT) motion over the common TB motion of the linear polymer to relax the strain from shear flow. [22][23][24][25][26] According to recent studies, the ring polymer has one more tank-treading (TT) motion over the common TB motion of the linear polymer to relax the strain from shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…DPD simulations were performed earlier for polymer solutions using bead-spring models 14 . However, recent BD simulations 15,16 have shown significant differences between the predictions of bead-spring and bead-rod models for an imposed flow field, even at the steady state. Thus, it becomes imperative to study the corresponding behaviour of bead-rod chains, where the solvent molecules are treated explicitly, as in DPD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, all EV interactions in conventional DPD is handled via soft potentials. In earlier BD simulations 16 , those were modeled by Lennard-Jones potentials, which diverges sharply at short distances. THus, it becomes imperative to check whether all scaling laws of polymer dynamics are reproduced by conventional DPD simulations.…”
Section: Introductionmentioning
confidence: 99%